BIYONGA RIVER FLOOD RISK ASSESMENT IN GORONTALO DISTRICT - Mutia
Most areas in Gorontalo Province are flooded every year. One of the affected areas is Gorontalo Regency. This flood causes residential areas, office buildings, agriculture, public facilities to be submerged and threatens lives. A flood risk study is needed to obtain the level of threat, capacity loss, risk and priority of flood disaster management. In this study, BNPB Regulation No. 2 of 2012 is used as a guideline for determining the index and level of flood risk. The determination of the priority scale uses PUPR Regulation No. 12 of 2014. Regional rainfall is calculated using the Thiessen Polygon method, while the planned flood discharge uses Q25th with the SCS method. Discharge data validation is carried out by overlaying inundation and flood height data with flood incident data obtained from BWS Sulawesi II Gorontalo. The 25-year return period flood in the Biyonga River is 129.16 m3/s. The results of the hydrological calculations are used in flood modeling using HEC-RAS 2D. The modeling results are in the form of a flood inundation area map of 136.12 ha in 4 sub-districts, namely Hepuhulawa, Hunggaluwa, Kayubulan, and Kayumerah. Based on the assessment of the level of threat, capacity loss and flood risk, all sub-districts are at high risk. The results of the flood management priority evaluation show that Hunggaluwa Sub-district has the highest level of loss compared to the other three (3) sub-districts with a score of 525 on a maximum scale of 600.